Guidelines for application of the United Nations Framework Classification for Ressources (UNFC) to uranium an thorium resources (United Nations, 2017)
This publication provides non-mandatory guidance for the application of the United Nations Framework Classification for Resources (UNFC) to uranium and thorium resources. These Guidelines are intended to assist all those responsible for finding, classifying, quantifying, financing, permitting, mining, and processing these minerals such that they are fit to enter the nuclear fuel cycle. With the rapidly changing uranium industry landscape and the changing UNFC framework, the guidelines are a work in progress. Updated reports and analyses will be issued in future to keep the application of UNFC to uranium resources more useful and relevant to the current realities.
Keywords: Anleitung; Graue Literatur; Amtsdruckschrift; Klassifikation; Uran; Thorium